2006
DOI: 10.1097/01.mlg.0000217238.84401.03
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Changes on the Morphology of the Otoconia

Abstract: The oldest rats showed the most degeneration of otoconia and linking filaments with otoconial fragments. This study of age-related morphologic changes in otoconia might help us understand the origin of idiopathic benign paroxysmal positional vertigo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 12 publications
9
94
1
2
Order By: Relevance
“…This is consistent with reported age-related changes in vestibular structure, biochemistry, and cardiovascular supply including pathology and loss of type I and type II hair cells (Rauch et al 2001;Shiga et al 2005;Park et al 1987), pathology of stereocilia/kinocilia (Rosenhall and Rubin 1975;Bloom and Hultcrantz 1994;Nakayama et al 1994), degradation of the cuticular plate (Anniko 1983;Bloom and Hultcrantz 1994), neural degeneration (Gleeson et al 1990;Rauch et al 2001), reduced blood flow (Lyon and Davis 2002), changes in the globular substance and otoconia (Jang et al 2006;Suzuki et al 1997;Campos et al 1990), and increased presence of lipofuscin (Rosenhall and Rubin 1975;Park et al 1987;Gleeson et al 1990;Anniko 1983). These structural observations represent human, rat, guinea pig, monkey, and C57BL/6 J inbred mice models.…”
Section: Discussionsupporting
confidence: 74%
“…This is consistent with reported age-related changes in vestibular structure, biochemistry, and cardiovascular supply including pathology and loss of type I and type II hair cells (Rauch et al 2001;Shiga et al 2005;Park et al 1987), pathology of stereocilia/kinocilia (Rosenhall and Rubin 1975;Bloom and Hultcrantz 1994;Nakayama et al 1994), degradation of the cuticular plate (Anniko 1983;Bloom and Hultcrantz 1994), neural degeneration (Gleeson et al 1990;Rauch et al 2001), reduced blood flow (Lyon and Davis 2002), changes in the globular substance and otoconia (Jang et al 2006;Suzuki et al 1997;Campos et al 1990), and increased presence of lipofuscin (Rosenhall and Rubin 1975;Park et al 1987;Gleeson et al 1990;Anniko 1983). These structural observations represent human, rat, guinea pig, monkey, and C57BL/6 J inbred mice models.…”
Section: Discussionsupporting
confidence: 74%
“…Aging has been associated with reduction in otoconia mass as well as fracture and fragment formation in both animals and humans (31)(32)(33)(34)(35). While it is easy to assume that reduction in otoconia would result in the reduction of organ function, otoconia degeneration has been shown to affect the utricle more than the saccule (31, 36), which would not explain the findings in the Agrawal et al study (27).…”
Section: Otolith Organscontrasting
confidence: 54%
“…In fact, it has been reported that autophagic activity decreases with age (53). This decrease may be related to the observed agerelated degeneration of vestibular otoconia, in which many features resemble those of autophagy-deficient mutants, including the presence of giant and abnormally shaped crystals (54). Thus, treatments aimed at maintaining normal autophagic activity in the elderly might constitute new approaches to the clinical management of balance-related disorders.…”
Section: Discussionmentioning
confidence: 99%